What does good care look like to people living with congenital heart disease in the 21st century? Qualitative online, asynchronous discussion forums - Christina Pagel; Jo Wray; Sonya Crowe; Louise Coats; Fiona Kennedy; Adrian H Chester (BMJ Open)
Objectives As part of a wider study, our aim was to elicit perspectives of people with congenital heart disease (CHD) and/or their parents/carers about their experiences of healthcare and what is important to them when receiving care.Design and setting A qualitative study involving a series of closed, asynchronous, online discussion forums underpinned by an interpretivist framework and set up and moderated by three patient charities via their Facebook pages.Participants People with CHD and parents/carers of people with CHD from the UK.Results Five forums were run for 12–24 weeks across the three charities, and 343 participants signed up to the forums. Four linked themes related to processes of care were identified following thematic analysis of the transcripts: relationships and communication; access and coordination; experience of discrete episodes of care and psychological support. These impacted how care was experienced and, for some patients, outcomes of CHD and its treatment as well as broader health outcomes. In addition, context relating to stages of the patient journey was described, together with patient-related factors such as patients’ knowledge and expertise in their own condition.Conclusions People with CHD and their parents/carers want individualised, person-centred care delivered within an appropriately resourced, multidisciplinary service. Although examples of excellent care were provided it is evident that, from the perspective of patients and parents/carers, some National Health Service Standards for people with CHD were not being met.